Experimental study on negative skin friction characteristics of double-sleeve pile - Wang Lu; Cao Yang; Liu Xianpeng; Chen Zhihua; Nie Zhichao (Scientific Reports)
Abstract Pile foundation structures are widely used in the construction of high-piled wharves in coastal soft soil areas due to their excellent adaptability to such environments. However, the extensive, deep backfilling involved in constructing these wharves can easily induce negative skin friction (NSF) on the piles, resulting in safety issues such as excessive settlement during the service life of the structures. This paper presents an indoor model experiment to examine the distribution of the THE NSF under varying pile-top loads and surcharge effects on single pile and double-sleeve pile foundations. The potential of double-sleeve pile foundations to mitigate the NSF was also explored. The results show that the axial force within the double-sleeve pile’s protected section remains essentially stable, though it is affected by the surface surcharge in the unprotected section. Time effect is exhibited both for the axial force and the NSF, gradually increasing over time. Compared to single piles, double-casing pile foundations can effectively isolate the down drag load caused by surrounding soil settlement, thereby reducing or eliminating the NSF on the pile sides.